A case report of neuroendocrine tumor (G3) at lower rectum with liver metastasis. Issue 38 (September 2018) - Yuan, Huayan; Yang, Yuanyuan; Wang, Wuyi; Cheng, Yong
Abstract: Rationale: Rectal neuroendocrine tumor is a rare disease that is difficult to diagnose by clinical and imageological examinations. The treatment of rectal neuroendocrine tumors is still controversial. Patient concerns: A 50-year-old woman complained of abdominal pain beneath the xiphoid process for 1 day. Physical checkup revealed tenderness at the right upper abdomen. A fecal occult blood test was positive. MRI showed an occupation lesion in the right lobe of the liver. Colonoscopy examination showed a lesion at the lower rectum with an ulcerated surface that was tough in texture. No abnormality was found in the tumor markers. Diagnosis: Rectal neuroendocrine tumor (G3) with liver metastasis. Interventions: Neoadjuvant chemotherapy followed by laparoscopic surgery was given. Outcomes: The patient followed up regularly in the outpatient department for 13 months after surgery, and no sign of recurrence was found. Lessons: Neoadjuvant chemotherapy followed by laparoscopic surgery is a new idea for the treatment of rectal neuroendocrine carcinoma with distant metastasis, which offers favorable conditions for saving the anus during the surgery to enhance the patient's quality of life.